Markedly improved overall survival in 10 consecutive patients with metastatic basal cell carcinoma. (30th August 2013) - Danial, C.; Lingala, B.; Balise, R.; Oro, A.E.; Reddy, S.; Colevas, A.; Chang, A.L.S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? The estimate of overall survival (OS) from date of diagnosis of distant metastatic basal cell carcinoma (BCC) to death is 8–14 months. This estimate was published in 1984 and needs to be updated. What does this study add? We explored OS in a series of patients from 1997 to 2011 at Stanford Hospital and Clinics. Our findings suggest that OS in patients with metastatic BCC may be more favourable than previously reported.